The Relationship between Employee Engagement and Employee Performance in Manufacturing at Pasir Gudang - Makwal, Siti Rahayu; Shahrul Nizam Salahudin, (Research in Management of Technology and Business, 2024)
In this era of globalization, employee engagement is recognized as one of the important variables that drive success organization in maintaining competitive advantage. Insignificant consideration has been given to employee engagement and its relationship with employee performance. Moreover, the limited studies that looking at employee performance does not integrate all dimensions of employee involvement. The focus of this study is to examine the level of employee involvement, identify the level of employee performance in the manufacturing field and examine the relationship between employee involvement in the manufacturing field and employee performance in a manufacturing company which is Kiswire Sdn Bhd, Kiswire Cord, Kiswire Dies and Kiswire Neptune located in Pasir Warehouse. This study uses quantitative techniques by submitting a questionnaire to obtain data using SPSS with a study sample of 375 respondents. The results of the study show that all objectives and hypotheses have been achieved and accepted. There is a significant positive relationship between employee engagement and employee performance. A suggestion for improvement for future studies is the scope of the study, which includes a larger population to obtain more descriptive validity and results. In conclusion, the important findings in this study can help the manufacturing sector in improving and reprogramming strategies to improve employee performance.